GOVERNANCE INNOVATIONS IN URBAN PLANNING: LEVERAGING SMART CITY TECHNOLOGIES FOR SUSTAINABLE DEVELOPMENT IN SOUTHEAST ASIAN METROPOLISES - Solong, Aras; Masriadi, Masriadi; Aras, Dzulkarnain (Department of Government, FISIP, Universitas Padjadjaran, 2024)
Metropolitan cities in Southeast Asia face significant challenges in achieving sustainable development amidst rapid urban growth. Governance innovations, leveraging smart city technologies, have emerged as potential solutions to address resource management issues and improve urban environmental quality. These technologies offer opportunities to improve efficiency and transparency in urban governance, but their implementation faces challenges such as infrastructure readiness and multi-stakeholder collaboration. This study aims to explore the impact of smart city technologies on sustainable development and evaluate the challenges and opportunities faced in their implementation in metropolitan cities in Southeast Asia. The research method used is a qualitative approach by collecting data from literature studies and relevant previous research. The collected data will be processed to identify patterns and relationships between smart city technologies and urban management. The results show that smart city technologies have significant potential in reducing carbon emissions, improving environmental quality, and increasing socio-economic welfare. However, the success of their implementation depends on the readiness of infrastructure and the collaborative capabilities of the government, private sector, and communities. Challenges such as limited telecommunication networks and financing need to be overcome so that the benefits of the technology can be optimally felt. Inclusive and sustainable implementation is essential to achieving sustainable development goals. Therefore, careful collaboration and planning are needed to ensure that smart city technologies can contribute positively to the growth of metropolitan cities in Southeast Asia.gb777